2022
DOI: 10.1038/s41598-022-22685-0
|View full text |Cite
|
Sign up to set email alerts
|

Loss of SATB2 expression correlates with cytokeratin 7 and PD-L1 tumor cell positivity and aggressiveness in colorectal cancer

Abstract: Colorectal carcinoma (CRC) is a disease that causes significant morbidity and mortality worldwide. To improve treatment, new biomarkers are needed to allow better patient risk stratification in terms of prognosis. This study aimed to clarify the prognostic significance of colonic-specific transcription factor special AT-rich sequence-binding protein 2 (SATB2), cytoskeletal protein cytokeratin 7 (CK7), and immune checkpoint molecule programmed death-ligand 1 (PD-L1). We analyzed a cohort of 285 patients with su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 84 publications
1
5
0
Order By: Relevance
“…Although the current study and other studies showed no significant association with sex, future studies with a large number of cases are indicated to confirm this result. Suvaitha et al [5], Ma et al [7], krudka et al [8], Schmitt et al [19], Mezheyeusk et al [20], and Dum et al [26] found a significant association of SATB2 with tumor site; the SATB2 loss was more commonly detected in tumors located in the right colon and cecum while SATB2-high tumors were more in left colonic tumors. Although the diffuse pattern of expression in the current study was more detected in the left colon and rectum, no significant association was detected.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the current study and other studies showed no significant association with sex, future studies with a large number of cases are indicated to confirm this result. Suvaitha et al [5], Ma et al [7], krudka et al [8], Schmitt et al [19], Mezheyeusk et al [20], and Dum et al [26] found a significant association of SATB2 with tumor site; the SATB2 loss was more commonly detected in tumors located in the right colon and cecum while SATB2-high tumors were more in left colonic tumors. Although the diffuse pattern of expression in the current study was more detected in the left colon and rectum, no significant association was detected.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, new biomarkers are required to distinguish highrisk cases and classify patients according to their prognosis [8]. Although a lot of studies are being done to identify the markers that help in detecting high risk cases and aid in choosing cases for adjuvant therapy, none of them has been shown to be good markers for routine clinical use [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different types of glandular and ductal epithelia contain CK7. Simultaneously, CK20 is abundantly expressed in mucosal cells of the gastrointestinal and urinary tracts (Hrudka et al, 2022). Tissue expression of CK15 was significantly linked with CRC subtype and stage.…”
Section: Cytokeratins (Cks)mentioning
confidence: 95%